2017
DOI: 10.1111/1759-7714.12572
|View full text |Cite
|
Sign up to set email alerts
|

Blocking transferrin receptor inhibits the growth of lung adenocarcinoma cells in vitro

Abstract: BackgroundTransferrin receptor (TfR) is expressed in most lung cancers and is an indicator of poor prognosis in certain groups of patients. In this study, we blocked cell surface TfR to inhibit lung adenocarcinoma (LAC) cell growth in vitro and investigated the associated molecular mechanisms to determine a potential therapeutic target in human LAC.MethodsRNA interference and antibody blocking techniques were used to block the function of TfR in LAC cells, and cell proliferation assays were used to detect the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The 2 −ΔCT method was used to determine the expression level of all messenger RNAs (mRNAs) (17). One-way analysis of variance was used for comparisons among three groups, and a P value <0.05 was considered statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…The 2 −ΔCT method was used to determine the expression level of all messenger RNAs (mRNAs) (17). One-way analysis of variance was used for comparisons among three groups, and a P value <0.05 was considered statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…1B, 1C). Commercially available CD71 mAb M-A712 has also been described before and was used to induce internalization of CD71 (6,24). However, cross-inhibition studies performed on Jurkat T cells revealed that mAb M-A712 recognizes a distinct CD71 epitope compared to VIP-1 or 5-528 (Supplemental Fig.…”
Section: Characterization Of the Cd71 Mabsmentioning
confidence: 99%
“…To our knowledge, no direct comparison of the uptake and antiproliferative activity of Tf-bound and unbound V in mammalian cells have been reported . In this study, we used a well-established model cell line, A549 (human lung epithelial carcinoma), that highly expresses human transferrin receptor 1 (TfR1) , to clarify the role of Tf binding in the biological activities of V. The interactions of V­(V/IV)–Tf adducts with TfR1 were also studied using a cell-free biolayer interferometry (BLI) model that was developed within our group. …”
Section: Introductionmentioning
confidence: 99%